A Novel Diabetes Prevention Intervention Using a Mobile App - Fukuoka, Yoshimi; Gay, Caryl L.; Joiner, Kevin L.; Vittinghoff, Eric (American journal of preventive medicine, 2015)
Mobile phone technology may be a cost-effective and convenient way to deliver proven weight-loss interventions and thereby prevent or delay onset of type 2 diabetes. The purpose of this study was to examine the feasibility and efficacy of a diabetes prevention intervention combined with a mobile app and pedometer in English-speaking overweight adults at risk for type 2 diabetes. RCT. Participants included 61 overweight adults with a mean age (SD) of 55.2 (9.0) years. Seventy-seven percent were women, 48% were racial/ethnic minorities, and baseline BMI was 33.3 (6.0). The curriculum was adapted from the Diabetes Prevention Program, with the frequency of in-person sessions reduced from 16 to six sessions and group exercise sessions replaced by a home-based exercise program. A study-developed mobile phone app and pedometer augmented the intervention and provided self-monitoring tools. Weight loss. Data were collected in 2012 and 2013 and were analyzed in 2014. In intention-to-treat analyses, the intervention group (n=30) lost an average of 6.2 (5.9) kg (–6.8% [5.7%]) between baseline and 5-month follow-up compared to the control group’s (n=31) gain of 0.3 (3.0) kg (0.3% [5.7%]) (p<0.001). The intervention group’s steps per day increased by 2,551 (4,712) compared to the control group’s decrease of 734 (3,308) steps per day (p<0.001). In comparison, the intervention group had greater reductions in hip circumference (p<0.001); blood pressure (p<0.05); and intake of saturated fat (p=0.007) and sugar-sweetened beverages (p=0.02). The intervention had no significant effect on fasting lipid or glucose levels. The significant weight loss resulting from this modified combined mobile app and pedometer intervention for overweight adults warrants further investigation in a larger trial.